The effect of joint auditing in narrowing the expectations gap: An analytical study of the auditors' viewpoints (Entrepreneurship Journal for Finance and Business, 2021)
The main objective of this research is to study the effect of applying the joint audit method in external audit offices by auditors in contributing to reducing and narrowing the emergence of the expectations gap in the performance of auditors. Because of its impact in reducing the expectations gap in auditing, the results of the field study indicated that there is a complete conviction on the part of the external audit offices of the importance of joint auditing. The results of the study were drawn from the field study with the hypothesis of the theoretical study, which indicated that there is an effect of joint auditing towards limiting the emergence of an expectations gap from the auditors' point of view. The local environment, which is no onger commensurate with the nature of some economic projects.